What Serverless Computing Is and Should Become: The Next Phase of Cloud Computing. - SCHLEIER-SMITH, JOHANN; SREEKANTI, VIKRAM; KHANDELWAL, ANURAG; CARREIRA, JOAO; YADWADKAR, NEERAJA J.; POPA, RALUCA ADA; GONZALEZ, JOSEPH E.; STOICA, ION; PATTERSON, DAVID A. (Communications of the ACM, 2021)
The article discusses the concept of serverless computing, which the authors believe is the next step in cloud computing. According to the article, serverless computing incorporates more than Function-as-a-Service (FaaS) aspects and will significantly alter how computer programmers work. The article also examines serverless cloud economics, research areas, and the possibility that serverless computing may fail.